Problems of Causation in Aquilian’s Casuistry - Bogunović, Mirjana B. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Roman lawyers interpreted causation in a very specific way, without any abstractions or generalisations, existence or non-existence of causation was established in each particular case ( ad hoc). They did not establish the existence of the causation between an act of a tortfeasor and a harmful result, but causation had to exist between the culpa of the tortfeasor and the result. Initially, it was necessary for the causation to be direct, made with active doing body to body (damnum corpori corpore datum). With the time, the narrow understanding of causation was overcome and indirect causation started to be appreciated, while the human behavior could exclusively be omissive. Aquilian’s casuistry is very rich with the cases of problematic causation. Meanwhile, these elementary rules for resolving a particular case in practice proved insufficient and incomplete, since unique life circumstances had created a need for a more complex view of causation.
Keywords: Lex Aquilia; actio in factum; simultaneously harmful effects; causa superveniens; Celsus; Julianus; causality